2016
DOI: 10.1158/1055-9965.epi-16-0339
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D Deficiency and Antinuclear Antibodies in Middle-Aged and Older U.S. Adults

Abstract: Background Vitamin D deficiency is associated with cancer and autoimmune diseases, but little is known about the association between vitamin D and antinuclear antibodies (ANA), a biomarker of immune dysfunction in healthy populations. The objective of this study was to determine if vitamin D deficiency is associated with ANA in middle age and older U.S. adults. Methods A cross-sectional analysis using the National Health and Nutrition Examination Survey (NHANES) 2001-2004 was conducted. Data was available fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
2
Order By: Relevance
“…Vitamin D levels may also be influenced by UV exposure ( 23 ). Lower vitamin D levels were previously found to be associated with ANA in middle aged and older adults in the NHANES (2001-2004) ( 24 ), but in the current study sample of younger adults and adolescents, higher vitamin D appeared positively associated with ANA (age-adjusted OR 1.43 for ≥75 versus 50-75 nmol/L). We saw no evidence of confounding by vitamin D levels; though in the summer sample the association of log 10 BP-3 with ANA appeared to be inverse, this may be due to chance or confounding or interactions with other unmeasured factors.…”
Section: Discussioncontrasting
confidence: 79%
“…Vitamin D levels may also be influenced by UV exposure ( 23 ). Lower vitamin D levels were previously found to be associated with ANA in middle aged and older adults in the NHANES (2001-2004) ( 24 ), but in the current study sample of younger adults and adolescents, higher vitamin D appeared positively associated with ANA (age-adjusted OR 1.43 for ≥75 versus 50-75 nmol/L). We saw no evidence of confounding by vitamin D levels; though in the summer sample the association of log 10 BP-3 with ANA appeared to be inverse, this may be due to chance or confounding or interactions with other unmeasured factors.…”
Section: Discussioncontrasting
confidence: 79%
“…In sensitivity analyses, we additionally controlled for country of birth, smoking status and household size, as these factors may influence exposure to hygiene hypothesis indicators, but the addition of these potential confounders did not meaningfully change effect estimates. Our previous work has shown that vitamin D deficiency was associated with ANA positivity in older US adults (aged 50+) (34). In the current study, however, no statistically significant differences in vitamin D levels by ANA status were observed, therefore it was not considered as a confounder.…”
Section: Discussioncontrasting
confidence: 72%
“…Similar to what has been previously described in ANA-positive healthy individuals [6,7] we hypothesized that an abnormal status of immunomodulatory vitamin D could play a role in anti-BP180-NC16A reactivity in healthy persons. In fact, hypovitaminosis D has been reported to be more common in AIBD patients than in the general population [8,9] but nothing is known about vitamin D and BP autoantibodies in healthy populations.…”
Section: Introductionmentioning
confidence: 56%